Teaching of communication at secondary schools in Mendoza: proposals for a critical approach to curriculum design - Llaver, Nora (2019)
This article shows the results of a research conducted in two stages between 2013 and 2017. In the first stage, the main objective was to reconstruct the representations of Social Communication teachers from secondary schools in Mendoza (Argentina) around teaching of communication. In the second stage, as a continuation of the previous one, the contents of the Provincial Curricular Design of the same subject were analyzed and resignified, taking into account the perspective of the critical media education (EMC). The assumption is that no media education can be called “critical” if the starting points when designing the processes of teaching and learning, and understanding the universe of media and technologies are not so. On the basis of the insights offered by the theories of resistance in education, critical curriculum theories and EMC, the contents on communication offered to school students are analyzed and challenged. This article is aimed at taking up again some questions that were part of the research: What is the critical dimension of media education? What pedagogical positions make it possible? What approaches should be prioritized in a really critical media education? How to question the curricular designs and schedules from a critical perspective to avoid the reproduction of hegemonic forms of communication?